P737 The use of infliximab therapeutic drug monitoring in virtual biologics clinic for inflammatory bowel disease (IBD) leads to clinically durable results. (16th January 2018) - Sagar, R; Lenti, M; Clark, T; Rafferty, H; Gracie, D; Ford, A; O'Connor, A; Hamlin, J; Ahmad, T; Selinger, C
Abstract: Background: We have previously shown that therapeutic drug monitoring (TDM) of infliximab (IFX) trough levels and anti-drug antibodies (ADAS) can aid decision-making for patients with IBD on biological therapy, if used in conjunction with clinical symptoms, disease history and other investigations. Until recently TDM was not universally available in the UK. The aims of this follow-up study were to evaluate 1-year outcomes of patients who had decisions changed on the basis of the results of TDM in our original study, and to test the hypothesis that TDM-based decisions to alter IFX treatment regimens or stop therapy are safe and durable. Methods: In our original study, a blinded treatment decision was first made, without knowledge of IFX trough and ADAs. Immediately after this, TDM results were released and a final treatment decision was recorded. For this study we collected 12-month follow-up data to investigate the long-term clinical outcomes of the decisions made. We compared patients with changed treatment decisions with those where the decision to continue IFX remained unchanged. We defined changed decision groups as (I) IFX stopped, (II) switch to other biological therapy, and (III) continue IFX with adjusted dose or interval. Events of interest were hospitalisation for IBD or further changes to biological therapy. Results: Of 190 patients reviewed in virtual biologics clinic 54 (28%) had decisions changed in the light of results of TDM. Of the 136 patients with an unchanged decision, 128 who continued IFX as previously dosed were used as the comparator group. There were no differences in hospitalisation rates between 3 changed decision groups (I, p = 1), (II, p = 0.2), (III, p = 0.4) and the unchanged decision comparator group (Table 1). Similarly, we found no differences in subsequent biologic therapy switches between 3 changed decision groups (I, p = 1), (II, p = 1), (III, p = 0.2) and the unchanged decision comparator group. Conclusions: Our study demonstrates that changes to IFX treatment based on the results of TDM were durable. Patients with a decision to stop, switch, or continue with an adjusted IFX dose experienced comparable clinical outcomes with those who continued IFX therapy unchanged. TDM-based decisions about IFX treatment that incorporate the clinical picture can safely alter therapy without exposing patients to an increased risk of hospitalisation or need for subsequent changes to biologic therapy.